Evaluation of mechanical wear in bismuth-titanium coatings synthesized by the sol-gel method and applied on 316 L stainless steel substrates (2019)
Steels are part of the basic equipment of most of the industrial framework, including very diverse sectors such as the oil, chemical and automotive industries. However, steels are susceptible to wear phenomena limiting their life in use and losing efficiency in the applications to which it is intended leading to a technological and economic problem. In mechanical systems, lubrication requires effective strategies to ensure that the increase in critical contact voltages does not cause material failure during operation. Although there are different ways to avoid the wear of steel parts, the development of material technology has allowed the manufacture of new alloys with anti-wear properties. Replacing steels with other higher cost materials is very unfeasible. For this reason, one of the alternatives of greatest interest to reduce wear is based on the surface modification of the metal through the use of coatings. The sol-gel method allows the manufacture of coatings on steel parts to reduce wear. The objective of this work was to manufacture, using sol-gel, bismuth-titanium coatings on 316 L stainless steel substrates in order to analyze the mechanical wear of the system and evaluate its wear rates and friction coefficients. The study focused on determining the effect of precursor concentration on performance as a film to reduce wear. It was determined that the friction coefficients show significant variations due to adhesive wear processes. With respect to wear, it is concluded that the coatings offer substrate protection by indicating wear rates lower than those reported for 316 L stainless steel substrates without coating.